The risk management system as the important part of good pharmacovigilance practices (GVP) - A. S. Kazakov (Безопасность и риск фармакотерапии, 2018)
The risk management system includes the process of determining the probability of occurrence of undesirable effects of pharmacotherapy, identifying the extent and magnitude of the risk analysis and the choice of risk management strategy, the selection of necessary for this risk management techniques and strategies of ways to reduce it. Thus, the risk management system is a modern and efficient pharmacovigilance tools aimed to improve the effectiveness and safety of pharmacotherapy.